Processus multi-acteurs de construction d’une éthique environnementale : le cas du système fluvial rhénan. - Céline Ohresser; Elodie Piquette; Nathalie Gartiser; Maurice Wintz (VertigO)
Considering the environmental ethics as an emerging quality of an anthropo-ecological system, this article aims to interpret the reorganization of what the authors named as « Rhine river system » in the context of an ecological crisis. Through the meeting of two disciplines (sociology and engineering design), an interpretative framework is suggested in order to explain the organization of communication and information process between the various self-referential systems. The main purpose of this article is to focus on the action of each system in conditioning at last the dissemination and the acceptance of an unique environmental ethics, understood as the recognition of the intrinsic properties of the Rhine river ecosystem, and adapted to the referents of each system involved.